CRIAÇÃO DE CD MULTIMÍDIA ENFOCANDO CONCEITOS E PROCESSOS PRODUTIVOS DE BIODIESEL NO BRASIL. MG - Maciel, Hagar Ceriane Costa Corsini (2010)
With the current major development in computer science, new methodologies have been used to improve the process of information dissemination. A perspective that cannot be ignored is the question of how to use these technologies to improve the teaching and learning process. One of these methodologies is the multimedia. This study, conducted in the laboratories of the Federal Institute of Informatics Sul de Minas, Campus Machado, MG, and in the José Rosário Vellano University, Campus Alfenas, MG, aims at demonstrating that the use of multimedia techniques, in parallel with all the resources it aggregates, may be a usefull and efficient tool, planned and developed to be a practical source of information collected in a sigle application of study on biodiesel. The Menu strategy, was used for navigation, where one chooses the option of acessing the contents without having to obey any predetermined order. Thus the users will free to access the contents in a dynamic, interactive and pleasant way, according to their interest or need, using audiovisual resources of easy operation and assimilation. The software was available for some students and teachers to evaluate the usability, readability, learning, teaching, multimedia elements, layout and interactivity. In general the software was assessed and satisfactorily met the user s expectations. In a scale of 2-10 points, for all variables studied, the average was above than 8.5 points. The CD-ROM of the biodiesel multimedia is a didactic material developed for educators and high school and college students.